GE_GERICHTE P/17611/2015 vom 9. Juli 2018 - GE Cour de justice (2018)
LÉSION CORPORELLE SIMPLE ; MENACE(DROIT PÉNAL) ; PEINE PÉCUNIAIRE ; TORT MORAL | CP.123; CP.180.al1; CP.41.al1.leta; CP.34.leta; CP.51; CO.47